Introduction of the HAM-Nat examination – applicants and students admitted to the Medical Faculty in 2012-2014 - Werwick, Katrin; Winkler-Stuck, Kirstin; Hampe, Wolfgang; Albrecht, Peggy; Robra, Bernt-Peter (GMS Zeitschrift für Medizinische Ausbildung, 2015)
Background/aim: In the 2012/13 winter semester, the Magdeburg Medical Faculty introduced a test of knowledge for the selection of applicants. The Hamburg Assessment Test for Medicine - Natural Sciences (HAM-Nat) comprises a multiple-choice test with questions on the aspects of biology, physics, chemistry and mathematics relevant to medicine, which was specifically developed for the selection of medicine applicants. The aim is to study how the HAM-Nat influences student selection, the reasons why students decide to take the test as part of their application procedure and what expectations they have of their course of study.Methods: The selection procedures applied at the university in 2011 (without HAM-Nat) and in 2012-2014 (with HAM-Nat) are compared. On the basis of the results of exploratory interviews, university entrants in winter semester 2013/2014 participated in a written survey on why they chose their subject and place of study and their expectations of their course of study. Results: No problems were encountered in introducing the extended selection procedure that included the HAM-Nat Test. The HAM-Nat had a great influence on the selection decision. About 65% of the students admitted would not have obtained a place if the decision had been based exclusively on their Abitur grade [grade obtained in the German school-leaving examination]. On average, male applicants obtained better HAM-Nat results than female ones. The questionnaire was answered by 147 out of 191 university entrants (77%). In the case of applicants from Saxony-Anhalt, the principle reasons for choosing the regional capital are its proximity, the social environment offered, good conditions for studying and the feel-good factor at the university. For the majority of applicants, however, particularly applicants from other federal states, the relatively good chances of admission in Magdeburg were the main reason. Conclusion: The Magdeburg Medical Faculty regards the HAM-Nat as a suitable tool for selecting applicants with outstanding knowledge of natural sciences and thus of increasing and harmonising levels of knowledge at the start of the course. Completion of the standard period of study and success in the 1st part of the German Medical Examination will be the subject of further observation of the students. The HAM-Nat, as a performance-related selection procedure, is not suitable for giving active preference to natives of Saxony-Anhalt in the application procedure but their number has increased since it was introduced. Applicants primarily use the selection procedure tactically to obtain the university place they want to study medicine. Specifics relating to curricula and university profile and research areas are not critical to their choice.